Primer Design and Analysis for Detection of mecA gene - Armini Syamsidi; Nuur Aanisah; Reyhan Fiqram; Imanuel Al Jultri (Journal of Tropical Pharmacy and Chemistry, 2021)
MecA is a gene that causes antibiotic resistance and it contained in Staphylococcus aureus. The gene can be detected using pairs of primer (forward and reverse). Primes is short nucleotide that are used as attachment point for DNA polymerase and as a barrier for the fragment DNA target to be amplified with Polymerase Chain Reaction (PCR). The aims of this study were to design and analysis the nucleotide primer sequences of MecA. This research using in silico method of NCBI (National Center of Biotechnology Information) application, clone manager10, oligoanalyzer3.1, perlprimer and primer3plus. The results of design and candidate primer analysis showed that the first candidate of forward and reverse primer that falls with in the criteria with base sequences 18-30, 40-60 GC%, Tm 50-60, 3’ dimer ?3, stability ?1,2, secondary structure >-16 Kcal/mol, runs ?5, repeats ?4, hairpins>-3 Kcal/mol. The conclusion is the first candidate of forward primer with 19 base pair (5’GTGAAGCAACCATCGTTAC'3), %GC 47Tm 58oC, 3’dimer 2, stability 1.6, secondary structure -1,95 dan -3,61 Kcal/mol, runs 2, hairpins -0,1 start 53844 and the first candidate of reverse primer with 21 base pair (5’CCTTCTACACCTCCATATCAC'3), %GC 47, Tm 58oC, 3’dimer 0, stability 1.3, secondary structure -4,74 dan -5,38 Kcal/mol, runs 2, hairpins -2.5 dan start 55852. The both of primer can be use for identification of MecA gene by PCR method